Competing discourses of built heritage: lay values in Irish conservation planning. Issue 3 (15th March 2016) - Parkinson, Arthur; Scott, Mark; Redmond, Declan
Abstract: Built heritage conservation has traditionally been shaped by professionals through an 'authorised heritage discourse', emphasising expert knowledge and skills, universal value, a hierarchy of significance, and protecting the authenticity of tangible assets. However, while the purpose of built heritage conservation is widely recognised to be broad, encompassing cultural, social and economic benefits, it takes place in the presence, and on behalf, of a wider public whose values and priorities may differ starkly from those of heritage power-players. Drawing on the perspectives of a range of built heritage actors in three small towns in Ireland, this paper contributes to these debates, exploring the competing values and priorities embedded within lay discourses of heritage. Based on critical discourse analysis of interviews with local actors, the paper identifies that collected memory and local place distinctiveness, contributing to a sense of local identity, are of central importance in how non-experts construct their understanding of built heritage. In the Irish context, this is particularly important in understanding social and cultural statutory categories of heritage interest. The paper concludes on the implications for policy and practice and, in particular, the need to more effectively take account of non-expert values and priorities in heritage and conservation decision-making.